Strategi Coping Stress pada Ibu Hamil di Masa Pendemi Covid 19 - Isnaeni Rofiqoch; Sawitri Dewi; Diah Atmarina Yuliani (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
Pregnancy is a time of determining the welfare and development of the fetus in the womb. During pregnancy many women experience psychological changes, so a method is needed to reduce the problems that arise during the pregnancy process, this method is called a coping strategy. The purpose of this study was to identify coping strategies for stress in pregnant women during the COVID-19 pandemic in the South Purwokerto Community Health Center, Banyumas Regency. This research is a qualitative research with a phenomenological approach. The data collection method in this research is carried out by in-depth interviews. This research is expected to be able to dig up information about what psychological problems are faced by pregnant women and how they solve the problems faced during the covid 19 pandemic. The main informant in the meantime is mother pregnant, supporting informants are midwives and family members (husband, mother or sibling) as triangulation. The results of this study stress coping strategies during pregnancy are needed to reduce problems during pregnancy. This strategy for coping with stress during pregnancy during the COVID-19 pandemic is carried out with the mechanism of Emotional Focused Coping and Problem Facus Coping. Although the Emotional Focused Coping mechanism is more dominantly used by pregnant women because pregnant women are women where women prioritize feelings over logic.